UTILIZATION OF @GREATMIND.ID ACCOUNT AS INFORMATION MEDIA ON LIFE TOPICS - Masya Afanda; Nina Yuliana (Ravine Publisher, 2024)
The @greatmind.id account provides information and inspiration from influencers and public figures as well as peace of mind through life wisdom from resource persons, which contains a collection of thoughts, aspirations and positive and motivational advice in accordance with world realities. The life that society is experiencing. Broad, in the form of quotes or digests in the form of articles on Instagram about various life topics. This research aims to discover how the @greatmind.id account is used as a medium for information about life topics. According to Pierre Levy, this research refers to new media theory, a qualitative approach that applies qualitative descriptive methods, namely, in-depth interviews, observations, and documentation. The research results found that the @greatmind.id account provides benefits for people who are experiencing something that is happening in their lives by providing a positive and motivating influence, both opening new perspectives in looking at life and making readers feel grateful. You and all things, as well as providing the best in conveying information about life topics for followers of the @greatmind.id account.